2016
DOI: 10.1186/1532-429x-18-s1-q57
|View full text |Cite
|
Sign up to set email alerts
|

Aortic flow and wall shear stress in aortic stenosis is associated with left ventricular remodeling

Abstract: Background Aortic stenosis (AS) can lead to highly variable stress for the left ventricle (LV) and consequently a broad range of LV remodeling. We hypothesize that changes in aortic blood flow caused by AS can contribute to cardiac afterload. The aim of this study was to describe the blood flow patterns in the ascending aorta in patients with AS and to determine its association with LV remodeling. Methods Thirty-seven patients with AS (14 mild, 8 moderate, 15 severe, age 63 ± 13 years) and 37 healthy, age-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Various advanced parameters can be derived from 4D flow MRI-acquired velocity data that may provide novel insight into aortic haemodynamics after TAVR, such as wall shear stress (WSS), flow eccentricity and flow displacement [5][6][7]. A recent histological study has shown that abnormal WSS results in increased deregulation of the aortic extracellular matrix and degeneration of elastic fibres, which may result in progressive aortic dilatation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various advanced parameters can be derived from 4D flow MRI-acquired velocity data that may provide novel insight into aortic haemodynamics after TAVR, such as wall shear stress (WSS), flow eccentricity and flow displacement [5][6][7]. A recent histological study has shown that abnormal WSS results in increased deregulation of the aortic extracellular matrix and degeneration of elastic fibres, which may result in progressive aortic dilatation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in 37 patients with various grades of aortic stenosis and 37 healthy volunteers, helical and vertical flow formations and flow eccentricity were assessed in the ascending aorta using four-dimesional flow CMR. 26 Compared with healthy volunteers, patients with aortic stenosis showed more frequently marked helical and vertical flow formation and eccentric flow with asymmetrical and elevated distribution of peak systolic wall stress in the ascending aorta. Smaller aortic orifice areas were associated with more vertical flow formation and eccentric flow and higher flow displacement whereas bicuspid aortic valve morphology was significantly associated with intense helical flow formation and higher flow displacement and peak systolic wall shear stress.…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 97%
“…25, 26 Koristeći se ovom tehnikom, Garcia i sur. 25 u 50 bolesnika s bikuspidnom i u 50 bolesnika s trikuspidnom valvulom i dilatiranom aortom pokazali su da bolesnici s bikuspidnom valvulom imaju višu vršnu vrijednost brzine protoka mlaza između izlaznog dijela LV-a i sinotubularnoga spoja u usporedbi s bolesnicima s trikuspidnom valvulom, unatoč sličnim dimenzijama aorte.…”
Section: Kardiovaskularna Magnetna Rezonancijaunclassified
See 2 more Smart Citations